IDENTIFIKASI JAMUR ASPERGILLUS SP PADA ROTI TAWAR YANG DIPERJUALBELIKAN DI DESA BUNGA EJAYA KECAMATAN PALLANGGA KABUPATEN GOWA - Rahmat Saleh; Hasra Ufiyana; Suharsih Thahir; Asnurbaety Dwiyana; Dita Ellyana Artha (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
White bread is a type of food made from wheat and fermented with yeast (Saccharomyces cerevisiae). The purpose of this study was to identify Aspergillus sp fungi in white bread sold in the community. The type of research used is descriptive by describing the results of observations that have been obtained. Sampling was carried out by purposive sampling, where the bread used was bread sold around Bunga Ejaya Village. The samples used in this study were 8 white breads obtained from several shops that were traded in Bunga Ejaya Village, Pallangga District, Gowa Regency. Based on the results of the study, it showed that of the 8 samples of white bread that had been observed, 7 white breads were declared positive for contamination with Aspergillus sp fungi and one sample was negative or not contaminated with Aspergillus sp fungi. The results of microscopic observations on white bread found several types of Aspergillus sp fungi, namely in sample codes RT1 and RT3 contained Aspergillus fumigatus fungi, RT2 and RT8 found Aspergillus terreus fungi, RT4, RT6, and RT7 found Aspergillus flavus fungi.